PENINGKATAN KINERJA PEGAWAI DALAM PROSES PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KANTOR KECAMATAN KELAPA DUA KABUPATEN TANGERANG PROVINSI BANTEN - Agung Nurrahman; Eko Budi Santoso; Muhammad Fadli Sani (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
This study focuses on improving the performance of employees in the Integrated District Administration Service (Paten) in Kelapa Dua District Office, Tangerang Regency, Banten Province. The research objective is to determine the performance of employees in the implementation of Integrated District Administration Services (PATEN). The research was conducted using descriptive qualitative method. The data collection technique was done by means of observation, interview and documentation. While the data analysis technique used begins with data reduction, data presentation, and drawing conclusions. The results showed that the Improvement of Employee Performance in the Integrated District Administration Service Process (Patent) at the Kelapa Dua District Office, Tangerang Regency, Banten Province in 2020 was relatively good. This can be based and can be proven by looking at several indicators of services that have been fulfilled and people who are satisfied with a service that is currently available. Based on the results of the study, the authors suggest improving the performance of the Kelapa Dua sub-district office employees by: first, it can increase the socialization and information about the District Integrated Administration Service to the village and sub-district communities in Kelapa Dua District. Second, emphasizing efforts to increase discipline, friendliness and courtesy of employees. Third, there is guidance and direction that has been carried out by the sub-district head to the Kelapa Dua District Office employees regarding the services and efforts that have been obtained.